La question de l’influence de la Qādiriyya sur les débuts du califat de Ḥamdallāhi, à l’épreuve de nouvelles sources - Bernard Salvaing (Afriques)
In their analysis of the movement launched by Aḥmad Lobbo in 1818, authors writing during the colonial period (such as Marty or Hampâté Bâ) projected to the past, in an anachronistic manner, the prominent role of Sufi brotherhoods as it had developed during their time. Hence, they attributed Aḥmad Lobbo’s movement to the influence of the Qādiriyya brotherhood and to the Kunta family. The study of local sources leads to dismiss this vision. In fact, the rise of the Islamic State in Māsina seems to take its roots in a revivalism that took as a reference the Islamic Policy of the Songhay Emperor Askiyā Muḥammad (d. 1538) who was advised by the preacher al-Maġīlī and tried to deeply integrate Islam into the religious and cultural life of the Empire. One must also take into account the long-standing presence, in the whole of Muslim West Africa, of an Islamic culture that focused on the study of fiqh and taṣawwuf, but without being rooted in institutionalized brotherhoods. Further, the Islamic renewal that took place in the rest of the Islamic World in the seventeenth and eighteenth centuries had little impact on West Africa, except perhaps in Sokoto. The real change in the matter occurred only with the coming of the Tiǧāniyya through al-Ḥāǧǧ ‘Umar.